The Impact of Quality Management on Job Satisfaction of Operating Theatre Department Employees of Valiasr Hospital in Tehran: A Participatory Action Research - Ali Mohammad Mosadeghrad; Mahnaz Afshari (Kerman University of Medical Sciences, 2016)
Introduction: Employees' job satisfaction has a significant effect on providing high quality services to patients. The aim of this study was to examine the impact of quality management on job satisfaction of Operating Theatre Department employees of Valiasr Hospital in Tehran in 2014. Methods: This participatory action research was performed on employees of Operating Theatre Department of Valiasr Hospital in Tehran in the first six months of 2014. Employees' job satisfaction was measured using a reliable questionnaire and the causes of employees' dissatisfaction were determined. Then, the employees' working processes and job satisfaction were improved using a ten-step quality management model provided by Mesdagh Rad. Employees' job satisfaction was statistically compared before and after the quality management intervention using SPSS 18. Results: Employees' job satisfaction was 51.2 percent. High work pressure, compressed shift schedule, high job stress, lack of organizational justice, reward system, and inappropriate encouragement, and lack of attention to the employees' needs, especially on the night shift, were the main causes of employees' dissatisfaction. Employees' satisfaction after intervention was 59.2 percent. The results showed that quality management improved employees' satisfaction by 15.6 percent. Employees' job satisfaction before and after the intervention was significantly different (P=0.000). Quality management principles such as management commitment, employees' empowerment, teamwork, trust and cooperation, effective communication, continuous training and learning, customer focus, and continuous quality improvement have positive effect on employees' job satisfaction. Conclusion: Implementing an appropriate quality management model enhances job satisfaction of hospitals employees. Keywords: Quality Management, Continuous Quality Improvement, Job Satisfaction, Hospital, Action Research Citation: Mosadeghrad AM, Afshari M. The Impact of Quality Management on Job Satisfaction of Operating Theatre Department Employees of Valiasr Hospital in Tehran: A Participatory Action Research. Journal of Health Based Research 2016; 2(2): 147-158.